Roda de capoeira: rito espetacular - Maira Cesarino Soares (2010)
This dissertation takes capoeira and its scenic potentiality as the object of study. With an approximation to the field of etnocenologia, this study has addressed the object capoeira and also analyzed some of its aspects. Besides the theoretical reference used, this research has also been based on the experience within capoeira rodas and lessons from Grupo Bantus Capoeira (the author has been a member of this group for over ten years), the observation of the discipline Capoeira Angola to UFMG Drama students during three semesters and the participation in capoeira rodas in Belo Horizonte (MG), Salvador (BA) and Mar Grande (BA). This study has also had the support of capoeira masters themselves, as well as some experts, to introduce the definition and a brief historic/background of the object. The main scenic aspects taken into account in capoeira were the game, the ritual, the spectacle, the performance and the improvisation. In order to analyze the ritual and the game of capoeira, Terrin (2004) and Huizinga (2007) have been used as a theoretical source. The capoeira roda has been studied as a ritual and also as a spectacle. The capoeira elements which are part of the scenic game, their spectacular and performing characteristics and their ritual behaviours have been analyzed. In order to do that, the concepts of spectacularity, theatricality proposed by Bião (1998, 2007a e 2007b) and performance discussed by Cohen (2002) e Schechnner (2003) have been considered. The scenic improvisation, as well as its principles presented by Johnstone (2000) and Muniz (2006a e 2006b) were reference to the study of improvisation in the game of capoeira. Finally, this study presents the possibilities regarding freedom of body expression through capoeira, by using as a reference the concept of joy as a power enhancer.